2000
DOI: 10.1021/bm000034z
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Molecular Weight Regulation, in Vitro, in Plant Species that Produce High and Low Molecular Weights in Vivo

Abstract: In three rubber-producing species, in vitro, the rates of initiation and polymerization and the biopolymer molecular weight produced were affected by the concentration of farnesyl diphosphate (FPP) initiator and isopentenyl diphosphate (IPP) elongation substrate (monomer). Ficus elastica, a low molecular weight-producer in vivo, synthesized rubber polymers approximately twice the molecular weight of those made by Hevea brasiliensis or Parthenium argentatum (which produce high molecular weights in vivo), possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 15 publications
4
42
0
Order By: Relevance
“…importantly, they demonstrated that increasing the amount of iPP while keeping the FPP concentration constant resulted in increased MW in three different types of WrPs: Hevea, guayule and Ficus elastica (Fig. 2.17) (Castillón and Cornish, 1999;Cornish et al, 2000). These findings support the notion of a living-like polymerization.…”
Section: 5supporting
confidence: 52%
“…importantly, they demonstrated that increasing the amount of iPP while keeping the FPP concentration constant resulted in increased MW in three different types of WrPs: Hevea, guayule and Ficus elastica (Fig. 2.17) (Castillón and Cornish, 1999;Cornish et al, 2000). These findings support the notion of a living-like polymerization.…”
Section: 5supporting
confidence: 52%
“…Natural rubber is composed of cis-1,4 polyisoprene with molecular weights ranging from <50 kDa in Ficus elastica to >1,000 kDa in H. brasiliensis (Cornish 1993;Castillón and Cornish 1999;Cornish et al 2000). Rubber biosynthesis takes place on the surface of rubber particles and is catalyzed by rubber-particle-bound cis-prenyltranferases (CPTs) via cis-1,4-polymerization of isoprene monomers derived from isopentenyl diphosphate (IPP).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the noncompetitive inhibition by 6 of H. brasiliensis rubber transferase may be caused by interference resulting from the additional binding of compound 6 at the IPP binding site, which is in the proximity of the allylic diphosphate binding site. Competition between IPP and allylic diphosphate for the IPP binding sites has been observed at high substrate concentrations [1,16], and 6 was present at a range of 2500 to 10 000‐fold molar excess to FPP in the assay (30‐ to 130‐times the K m for FPP [17]). These results suggest that the spatial orientation between the IPP and initiator binding sites differs between the two rubber transferases, as well as the ability to bind 6 at other surfaces within the active site.…”
Section: Discussionmentioning
confidence: 99%
“…The different behavior between the two rubber transferases towards 6 should also be considered in light of the cooperative effects between IPP and FPP if one assumes that 6 is perceived as FPP by both enzymes. In the range of concentrations of 6 incubated in the assays, the two rubber transferases exhibit different degrees of negative cooperativity, with the P. argentatum enzyme showing the strongest effect [17]. Under these conditions, binding of the first initiator molecule decreases the ability of a free FPP to displace the bound FPP (or elongating polymer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation